From the Editors - Chief, Editor in (University of Muhammadiyah Prof. DR. HAMKA, 2016)
Welcome to the July 2016 issue of Journal of ELT Research. There are two special moments accompanying this issue: Ramadan & Eid al-Fitr and Indonesian Independence Day. These two big events remind us on their great spirit. The former, Ramadan & Eid al-Fitr, teaches us how to experience hunger and thirst, thus enabling us to reflect on the lives of the needy, while the latter teaches us how resiliency and determination can free us from oppression. As regards, doing and writing research requires reflection and determination. We, ELT practitioners and researchers, need to always reflect on challenges facing students and be determined to tackle the challenges. Our July issue touches diverse topics surrounding the challenges of ELT. It is important to note that there are some corrections on the page numbers from the previous galley.